Dyadic effects of distress on sleep duration in advanced cancer patients and spouse caregivers. Issue 12 (12th November 2019) - Otto, Amy K.; Gonzalez, Brian D.; Heyman, Richard E.; Vadaparampil, Susan T.; Ellington, Lee; Reblin, Maija
Abstract: Objective: Short sleep duration is a common problem for both advanced cancer patients and their spouse caregivers. Sleep and distress have been shown to be interdependent in patient‐caregiver and spouse dyads, yet virtually, no work has explored the dyadic effects of psychological distress on sleep in advanced cancer patients and spouse caregivers. The goal of the present study was to examine the dyadic impact of anxiety and depression on sleep duration in a sample of advanced cancer patients and their spouse caregivers. It was hypothesized that, for both patients and caregivers, anxiety and depression in individuals would be associated with sleep duration in both themselves (actor effects) and in their spouses (partner effects). Method: Advanced cancer patients and their spouse caregivers (N = 87 dyads) completed cross‐sectional questionnaires assessing demographic variables, subjective health, subjective sleep duration, and anxiety and depression symptoms. Results: Controlling for sex, age, and subjective health, individuals' anxiety was negatively associated with their own and their partner's sleep duration. No significant actor or partner effects were found for depression. Conclusions: Results provided partial support for hypotheses. Although past work has demonstrated links between subjective sleep disturbance and anxiety/psychological distress, this is one of the first studies to examine partner effects of distress on sleep disturbance in advanced cancer patients and spouse caregivers.